An inter-laboratory comparison of different analytical methods for the determination of monomethylmercury in various soil and sediment samples: A platform for method improvement. (February 2017) - Kodamatani, Hitoshi; Balogh, Steven J.; Nollet, Yabing H.; Matsuyama, Akito; Fajon, Vesna; Horvat, Milena; Tomiyasu, Takashi
Abstract: An inter-laboratory study was conducted to compare results from different analytical methods for monomethylmercury (MeHg) concentrations in 17 soil and sediment samples. The samples were collected from mercury-contaminated areas, including Minamata Bay and Kagoshima Bay in Japan, the Idrija mercury mine in Slovenia, and an artisanal small-scale gold mining area in Indonesia. The Hg in these samples comes from several different sources: industrial waste from an acetaldehyde production facility, volcanic activity, Hg mining activity, and artisanal and small-scale gold mining activity (ASGM). MeHg concentrations in all the samples were measured in four separate laboratories, using three different determination methods: Kagoshima University (Japan), using high-performance liquid chromatography–chemiluminescence detection (HPLC-CL); National Institute for Minamata Disease (Japan), using gas chromatography–electron capture detection; and Metropolitan Council Environmental Services (USA) and Jozef Stefan Institute (Slovenia), both using alkylation-gas chromatography–atomic fluorescence spectrometry detection. The methods gave comparable MeHg results for most of the samples tested, but for some samples, the results exhibited significant variability depending on the method used. The HPLC-CL method performed poorly when applied to samples with elevated sulfur concentrations, producing MeHg concentrations that were much lower than those from the other methods. Additional analytical work demonstrated the elimination of this sulfur interference when the method was modified to bind sulfur prior to the analytical step by using Hg 2+ as a masking agent. These results demonstrate the value of laboratory intercomparison exercises in contributing to the improvement of analytical methods. Graphical abstract: Highlights: Three different methods for the determination of MeHg in soils and sediments were compared in an inter-laboratory study. The various analytical methods yielded comparable results for most of the soil and sediment samples. Higher analytical variability was observed for samples containing higher concentrations of S. The results were used to modify and improve a new liquid chromatography method.